Safety and efficacy of the combination of selpercatinib with osimertinib in NSCLC: a case report and review of the literature - Resuli, Blerina; Galarza, Heidi; Kauffmann-Guerrero, Diego; Oversohl, Julian; Behr, Jürgen; Tufman, Amanda (Frontiers in Oncology, 2025)
Osimertinib, a third-generation epidermal growth factor receptor–tyrosine kinase inhibitor (EGFR-TKI), has demonstrated significant clinical activity and tolerability in EGFR-positive non-small cell lung cancer (NSCLC) patients. However, acquired resistance to osimertinib is inevitable, and the mechanisms underlying resistance to third-generation EGFR-TKIs remain complex and not fully understood. In this case, we report a patient with EGFR-mutated NSCLC who progressed on first-line osimertinib treatment, acquiring a nuclear receptor coactivator 4–rearranged during transfection (NCOA4–RET) fusion alongside a co-mutation in the tumor protein p53 (TP53) gene. Despite these genomic alterations, the patient derived notable clinical benefit from the combination of osimertinib and selpercatinib, suggesting that this dual therapy may offer a promising approach to overcoming resistance in such cases.